Review: Pemanfaatan Vakum pada Solar Still dalam Proses Laju Penguapan Air Laut untuk Pengaplikasian Desalinasi Kolam Garam - Irfan Maulana Yusuf; Dan Mugisidi (Prosiding Seminar Nasional Teknoka, 2025)
Vacuum is a condition of air pressure lower than atmospheric pressure and has a significant influence on the process of changing the liquid phase to vapor. Vacuum pressure has a direct influence on increasing the rate of seawater evaporation by lowering the boiling point so that the evaporation process can occur at a low temperature. This study aims to analyze the effect of vacuum pressure on the rate of seawater evaporation for application in a salt pond desalination system. The method used is a literature review from various journals discussing the application of vacuum in the seawater desalination process. The results of the study indicate that reducing pressure significantly accelerates the rate of evaporation and reduces the need for heat energy. The application of vacuum pressure is considered effective in improving performance and efficiency compared to atmospheric pressure systems. This study can provide the development of an energy-efficient desalination system that can be potentially applied in coastal areas.